Prevalence and association of asthma and allergic sensitization with dietary factors in schoolchildren: data from the french six cities study. (December 2015) - Saadeh, Danielle; Salameh, Pascale; Caillaud, Denis; Charpin, Denis; De Blay, Frédéric; Kopferschmitt, Christine; Lavaud, François; Annesi-Maesano, Isabella; Baldi, Isabelle; Raherison, Chantal
Abstract Background The prevalence of asthma and allergy has recently risen among children. This increase in prevalence might be related to various factors, particularly diet. The aim of this study is to assess the prevalence and association of asthma and allergic sensitization with dietary factors in the French Six Cities Study. Methods Cross-sectional studies were performed among 7432 schoolchildren aged 9–11 years in Bordeaux, Clermont-Ferrand, Créteil, Marseille, Reims, and Strasbourg. Parental questionnaires, based on the International Study on Asthma and Allergies in Childhood (ISAAC), were used to collect information on allergic diseases and potential exposure factors including a food frequency questionnaire to evaluate dietary habits. Skin prick testing to common allergens for allergic sensitization and bronchial hyper-responsiveness (BHR) testing to exercise were performed. Confounders control was performed with multiple logistic regressions. Results Asthma symptoms, asthma and allergic sensitization were more prevalent in boys than in girls and were more prevalent in the South than in the North of France. After adjustment for confounders, fruit juice intake was associated with a low prevalence of lifetime asthma (ORa [95 % CI]; 0.73 [0.56–0.97]), butter intake was positively associated with atopic wheeze (1.48 [1.07–2.05]) and having lunch at the canteen 1–2 times/week compared to never or occasionally was associated with a lower prevalence of past year wheeze (0.71 [0.52–0.96]), lifetime asthma (0.76 [0.60–0.96]) and allergic sensitization (0.80 [0.67–0.95]). Meat intake was inversely related to past year wheeze among atopic children (0.68 [0.50–0.98]) while fast food consumption and butter intake were associated with an increase prevalence of asthma (2.39 [1.47–3.93] and 1.51 [1.17–2.00] respectively). Fish intake was associated with a lower prevalence of asthma among non-atopic children (0.61 [0.43–0.87]. None of the dietary factors was associated with BHR. Conclusions Diet is associated with wheeze, asthma and allergic sensitization but not with BHR in children. These results provide further evidence that adherence to a healthy diet including fruits, meat and fish seems to have a protective effect on asthma and allergy in childhood. However, prospective and experimental studies are needed to provide causal evidence concerning the effect of diet on asthma and atopy.